2005
DOI: 10.1024/0301-1526.34.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Importance of early repair of isolated abdominal aortic dissecting aneurysm

Abstract: Symptomatic patients or patients at good risk should undergo surgical repair earlier than in the case of abdominal aortic aneurysm without dissection (AAA). Dissection in addition to an AAA will further increase the weakness of the aortic wall and the possibility of aortic rupture will become higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Ten studies reported different treatment strategies, including conservative treatment, ENDO and OS 3,7,8,10,13,15e18,26 ; six studies only reported ENDO 9,14,19e21,25 and one study only reported OS. 11 The details of the main characteristics of included studies are summarised in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies reported different treatment strategies, including conservative treatment, ENDO and OS 3,7,8,10,13,15e18,26 ; six studies only reported ENDO 9,14,19e21,25 and one study only reported OS. 11 The details of the main characteristics of included studies are summarised in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…During follow up, other than two deaths before treatment and 35 deaths in the Kang et al 13 study with non-separated data, 21 deaths The overall 91% of IAADs were spontaneous, which is comparable to previous studies reporting dissection types (66.7e100%). 3,7,9,11,14,18,19,21,25,26 Hypertension, smoking, and hyperlipidaemia were the most common concomitant risk factors of IAAD, which could induce endothelial damage and a persistent inflammatory response to stimulate formation of atherosclerosis and spontaneous aortic dissection. 27,28 Therefore, all patients with IAAD should be advised on basic lifestyle interventions, including hypertension control, smoking cessation, and a decrease of salt and fat in diet.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…7 Generally, however, dissecting AAAs are more clinically evident than their non-dissecting counterparts because of their rapid evolution, although the presenting symptoms may initially be heterogeneous and non-specific. 8 Although the natural history and management of this combined pathology is poorly understood, the presence of both aneurysmal disease and aortic dissection is associated with a significant risk of vessel rupture due to loss of integrity of the aortic wall and increased wall tension. Although debate exists about when these patients should be offered intervention, a review of the literature appears to favour early surgical repair 9 and probably at an aneurysm size of just 3 cm, considerably below the usual 'cut-off' of 5.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…7 Generally, however, dissecting AAAs are more clinically evident than their non-dissecting counterparts because of their rapid evolution, although the presenting symptoms may initially be heterogeneous and non-specific. 8…”
Section: Discussionmentioning
confidence: 99%
“…14,21,22) This tendency is due to a decrease in elastin in the aortic wall from the chest to the abdomen. 20) However, in the abdominal aorta unlike the thoracic aorta, changes in the media such as cystic medial necrosis rarely occur, and the presence of PAU may be closely associated with the development of abdominal aortic dissection. The onset of this dissection is often acute with symptoms such as abdominal and low back pain, but some cases are asymptomatic and incidentally detected.…”
Section: Resultsmentioning
confidence: 99%